SOCIAL PROTEST IN INDIA - S. I. Lunev (Vestnik MGIMO-Universiteta)
Economic globalization creates unfavorable conditions for some countries and social groups while the situation in other countries and social is becoming worse. That is why social problems are on the rise worldwide. Thus, social protest became the major cause of the Arab spring is. Social wave overwhelmed Western Europe and the USA. The solution of social problems depends not on the political will of the elite, but on the activity of the population, as the ruling circles will not adopt a policy of self-restrictions and concessions to the majority without the hard push from the bottom. The peculiar feature of India is the general satisfaction of the society with the political system and economic situation. At the same time the protests against specific cases and events in the country mobilize hundreds of thousands of people, be it corruption scandals or violence against women. However, cultural- civilizational factors contribute to the non-violent character of almost all mass actions. Another distinctive feature of India is the desire of the organizers of the protest to reject support of the major parties due to the belief that political leaders are interested more in strengthening their social base rather than in solving the concrete problems. There are different categories of social protest in India: peasant movements; scheduled castes' (Dalits, the former untouchables) movements; anti-corruption movements; environmental movements; backward caste movements; women's movements; tribal movements; industrial proletariat movements; students' movements; middle class movements; human rights movements. The first four movements are currently the most noticeable. Social protest has not, so far, led to any serious political instability. However, a certain development of the situation can generate it, as well as the rejection of the mainly peaceful methods. In this respect, Dalit movements, especially in case of further erosion of the caste system, are the subject of the greatest concern.